Human Papillomavirus Typing in HIV-Positive Women. Issue 2 (2001) - Hameed, Meera; Fernandes, Helen; Skurnick, Joan; Moore, Dorothy; Kloser, Patricia; Heller, Debra
Abstract : Objective: Human papillomavirus (HPV) is the major cause of cervical carcinoma and cervical intraepithelial neoplasia worldwide. Certain HPV types have a strong association with and probably a causative role in the pathogenesis of premalignant cervical lesions. Epidemiologic studies in women infected by the human immunodeficiency virus (HIV) have shown an increased incidence of squamous intraepithelial lesions (SILs), whichwere predominantly high-grade. Six to 30 per cent of women diagnosed with atypical squamous cells of undetermined significance (ASCUS) on a Papanicolaou (Pap) smear harbor SIL in normal screening populations. This study was undertaken to determine the presence of low- and high-risk HPV types in women infected by HIV and to correlate the results to those of the Pap smear. Study design: HPV DNA typing (low- and high-risk) by Digene™ (Digene Corporation, Gathesburg, MD) hybrid capture methodology was performed on cervical swabs from 209 HIV-positive women. The results of HPV typing were correlated with those of the Pap smear in a retrospective analysis. Results: One hundred and one women (48%) tested positive for HPV subtypes by DNA typing by the hybrid capture method. Of these, 64 patients (63%) had Pap smears whichwere read as being normal, having benign cellular changes, or having ASCUS (favor reactive process). Of these, 19 patients tested positive for both high-risk and low-risk subtypes, 32 patients tested positive only for high-risk subtypes, and 13 patients tested positive only for low-risk subtypes. Conclusion: HPV subtyping identifies a significant group of HIV-positive women who are at risk for developing cervical intraepithelial neoplasia, although they may not show significant abnormalities on their Pap smears.